Faktor Minat Peserta Didik Dalam Mengikuti Layanan Konseling Individual di Kelas XI IPS SMA Negeri 3 Pariaman - Fira Yuni Darti; Mori Dianto; Wira Solina (Departement of Mathematics Education, 2023)
The background of this research is that there are students who are hesitant to take part in individual counseling, there are students who are afraid to take part in individual counseling and there are students who prefer to tell stories to friends rather than the counseling teacher. The purpose of this study was to describe the interest factors of students in participating in individual counseling services in class XI IPS SMA Negeri 3 Pariaman seen from: 1) Knowledge. 2) Observation, 3) Perception. 4) Attitude. This research was conducted using a quantitative descriptive method. The study population was 34 students who were selected by purposive sampling technique with 34 participants. The instrument used is a questionnaire. As for data analysis using interval scores and percentages. Based on the results of research on the interest factors of students in participating in individual counseling services in class XI IPS SMA Negeri 3 Pariaman seen from: 1) The knowledge factor of students in participating in individual counseling services is in the high category. 2) Student observation factors in participating in individual counseling services are in the many categories, 3) Perceptual factors of students in participating in individual counseling services are in the high category. 4) The attitude factor of students in participating in individual counseling services is in the high category. It is recommended that counseling teachers provide an understanding of individual counseling to students in an interesting way so that students understand the benefits of getting individual counseling services.